2020
DOI: 10.1155/2020/7149408
|View full text |Cite
|
Sign up to set email alerts
|

S100A9 Increases IL‐6 and RANKL Expressions through MAPKs and STAT3 Signaling Pathways in Osteocyte‐Like Cells

Abstract: Objective. Calprotectin is a heterocomplex of S100A8 and S100A9 and is mainly secreted from neutrophils, monocytes, and chondrocytes in inflammatory condition. Calprotectin binds to RAGE and TLR4 and induces the expression of proinflammatory chemokines and cytokines in various cells. Periodontitis is a chronic inflammatory disease that leads to gingival inflammation and alveolar bone resorption. Calprotectin levels in gingival crevicular fluid of periodontitis patients are higher than healthy patients. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Neutrophils can produce proteins, including S100A9, IL‐1, IL‐6, and TNF, that stimulate RANKL expression 37‐39 . These proteins secreted from neutrophils may increase RANKL expression in osteoblasts, PDL cells, osteocytes, and lymphocytes, resulting in subsequent increased RANKL expression in periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils can produce proteins, including S100A9, IL‐1, IL‐6, and TNF, that stimulate RANKL expression 37‐39 . These proteins secreted from neutrophils may increase RANKL expression in osteoblasts, PDL cells, osteocytes, and lymphocytes, resulting in subsequent increased RANKL expression in periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils can produce proteins, including S100A9, IL-1, IL-6, and TNF, that stimulate RANKL expression. [37][38][39] These proteins secreted from neutrophils may increase RANKL expression in osteoblasts, PDL cells, osteocytes, and lymphocytes, resulting in subsequent increased RANKL expression in periodontal tissue. Air pouch exudates showed increased numbers of CD11b + Ly6G + RANKL + neutrophils following LPS injection and reduced CD11b + Ly6G + RANKL + neutrophil numbers following anti-Ly6G Ab administration in LPSinjected air pouches.…”
Section: F I G U R E 4 Reduction Of Ranklexpressing Neutrophils In Exmentioning
confidence: 99%
“…Immunohistochemistry and RNA sequencing showed that S100A8 and S100A9 were highly expressed in the ligatureinduced PD (Maekawa et al, 2019). After mouse osteocyte-like cells (MLO-Y4-A2) were treated with S100A9, the expression of IL-6 and RANKL increased, and the p38/ERK/STAT3 signaling pathway was activated, indicating that alarmins were involved in periodontal bone destruction (Takagi et al, 2020). It is worth noting that the levels of S100A12 and C-reactive protein in the gingival crevicular fluid and serum of patients with PD are elevated and positively correlated with periodontal parameters (Pradeep et al, 2014), suggesting that alarmins may be the link between PD and AS.…”
Section: Alarminsmentioning
confidence: 99%
“…S100A8 and S100A9, two proinflammatory calcium-binding S100 proteins acting as damageassociated molecular patterns, were implicated in pathogenesis of rheumatic diseases having strong associations with the disease activity and potential as therapeutic targets (Austermann et al, 2018). S100A9 was also reported to increase IL-6 production and RANKL expression in osteocyte-like cells suggesting potential as osteoimmune biomarker for inflammatory osteolysis (Takagi et al, 2020).…”
Section: Diagnostic Devices Salivary Proteome and Salivary Genomementioning
confidence: 99%